If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(7x + -4) + -1(6x + -6) + 7 = -12(x + -1) + -1(4x + 13) + 3 Reorder the terms: -1(-4 + 7x) + -1(6x + -6) + 7 = -12(x + -1) + -1(4x + 13) + 3 (-4 * -1 + 7x * -1) + -1(6x + -6) + 7 = -12(x + -1) + -1(4x + 13) + 3 (4 + -7x) + -1(6x + -6) + 7 = -12(x + -1) + -1(4x + 13) + 3 Reorder the terms: 4 + -7x + -1(-6 + 6x) + 7 = -12(x + -1) + -1(4x + 13) + 3 4 + -7x + (-6 * -1 + 6x * -1) + 7 = -12(x + -1) + -1(4x + 13) + 3 4 + -7x + (6 + -6x) + 7 = -12(x + -1) + -1(4x + 13) + 3 Reorder the terms: 4 + 6 + 7 + -7x + -6x = -12(x + -1) + -1(4x + 13) + 3 Combine like terms: 4 + 6 = 10 10 + 7 + -7x + -6x = -12(x + -1) + -1(4x + 13) + 3 Combine like terms: 10 + 7 = 17 17 + -7x + -6x = -12(x + -1) + -1(4x + 13) + 3 Combine like terms: -7x + -6x = -13x 17 + -13x = -12(x + -1) + -1(4x + 13) + 3 Reorder the terms: 17 + -13x = -12(-1 + x) + -1(4x + 13) + 3 17 + -13x = (-1 * -12 + x * -12) + -1(4x + 13) + 3 17 + -13x = (12 + -12x) + -1(4x + 13) + 3 Reorder the terms: 17 + -13x = 12 + -12x + -1(13 + 4x) + 3 17 + -13x = 12 + -12x + (13 * -1 + 4x * -1) + 3 17 + -13x = 12 + -12x + (-13 + -4x) + 3 Reorder the terms: 17 + -13x = 12 + -13 + 3 + -12x + -4x Combine like terms: 12 + -13 = -1 17 + -13x = -1 + 3 + -12x + -4x Combine like terms: -1 + 3 = 2 17 + -13x = 2 + -12x + -4x Combine like terms: -12x + -4x = -16x 17 + -13x = 2 + -16x Solving 17 + -13x = 2 + -16x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '16x' to each side of the equation. 17 + -13x + 16x = 2 + -16x + 16x Combine like terms: -13x + 16x = 3x 17 + 3x = 2 + -16x + 16x Combine like terms: -16x + 16x = 0 17 + 3x = 2 + 0 17 + 3x = 2 Add '-17' to each side of the equation. 17 + -17 + 3x = 2 + -17 Combine like terms: 17 + -17 = 0 0 + 3x = 2 + -17 3x = 2 + -17 Combine like terms: 2 + -17 = -15 3x = -15 Divide each side by '3'. x = -5 Simplifying x = -5
| ab+ac-4b-4c=0 | | -6+2-5= | | (z^2+2z-8)(z+2)=0 | | (z^3+2z^2-8z+2)(z^2+2z-8)=0 | | (5c-4)(6c-6)= | | 4(3x-1)-3(2x+1)=1-7x | | 80x^2+80x+11=0 | | 2a^2+12a=-32 | | 4x-2=3x-10 | | 3s^2+2s-21=0 | | y^2+2y=-10 | | -8y^2+2-y=0 | | y^2+2y+10=0 | | 3x+2x+1=5(x+2)+1 | | 3(x-2)+3x=1-(2x+5) | | 3c^2+23c+40=0 | | 3x+2=3(x+4)+1 | | 3y^3-10y^2+3y= | | 3(x-2)+3x=1-2x+5 | | -4(x+-4)=5x+3 | | -4(x-4)=5(x+3) | | 7y^3+36y^2+5y= | | c(x)=0.5x^2+0.4x+4.826 | | x(x-2)(x+3)=266 | | (x+4)+x+(2x-10)=46 | | 70b^2-3ab-a^2=0 | | x^3+x^2-6x-266=0 | | 3x^2-x-52=0 | | c^2-36c= | | 3x^2+8x=x^2-x-10 | | a^2-7a-8=0 | | 4x-y=z |